Antibiotic Resistance and Therapeutic Efficacy of Helicobacter pylori Infection in Pediatric Patients-A Tertiary Center Experience - Felicia Galoș; Cătălin Boboc; Mara-Ioana Ieșanu; Mălina Anghel; Andreea Ioan; Elena Iana; Maria Teodora Coșoreanu; Anca Andreea Boboc (MDPI AG, 2023)
One of the most widespread bacterial infections worldwide, Helicobacter pylori is thought to affect almost half of the world's population. Due to rising antibiotic resistance, treatment should be tailored according to antibiotic susceptibility testing (AST). This study aims to evaluate Helicobacter pylori antibiotic resistance and its therapeutic efficacy in children. We conducted a prospective, single-center study, that evaluated 68 children referred for upper gastrointestinal endoscopy (UGE) following chronic dyspeptic syndrome. Each patient underwent multiple biopsies to perform bacterial cultures with AST and histopathological examinations for the diagnosis. Patients without antibiotic resistance or negative cultures received a 10-day sequential therapy, while the others had the antibiotic regimen tailored based on AST. Fifty-nine patients with a positive biopsy-based diagnosis (24 males) were finally included. Bacterial cultures with AST were positive for 13 patients (22.03%) and the antibiotic resistance for clarithromycin was 15.38%. Fifty-seven patients were administered sequential therapy with an eradication rate of 94.73%. Clarithromycin-resistant patients were successfully treated with 10-day triple therapy of esomeprazole, amoxicillin, and metronidazole. Although bacterial cultures had a low positivity rate, sequential therapy had a successful eradication rate. Further studies are necessary to better assess Helicobacter pylori antibiotic resistance to provide tailored treatment and identify children that need closer monitoring.